Impacts of the Thondaimanaru Barrage Construction on Socio – Economic Status of Fishing Communities in Thondaimanaru Lagoon, Jaffna, Sri Lanka - Shobiya, P.; Sivashanthini, K.; Sutharshiny, S.; Gunaalan, K. (My University, 2019)
Present study was conducted to determine the impacts of barrage construction on livelihood status of fishers who involve fishing in Thondaimanaru lagoon. The data related to the socio - economic condition of fishers in the particular area were obtained through a pre - tested structured questionnaire and in - depth guided interviews from July 2016 to January 2017. Randomly selected 25 fishermen were interviewed. The collected data were subjected to descriptive statistical analysis. Survey results indicated that 88% of fishermen are living as nuclear families consisting of 4 - 5 members. Majority of fishermen are Hindus and 92% are married. About 64% engaged in fishing are under age group of 36 - 55. Education is still not prominent among the fishers. Only 84% has primary education. The main occupation in this society is fishing and earned highest monthly income LKR (6000 ± 1000). It was found that installation of barrage plays a crucial role in socio - economic status of fishers of Thondaimanaru lagoon. This barrage severely affected the traditional fishing, amount of fish production and its consequences on their income as well. It was apparent from the current study that these fishermen have poor livelihood status and they need support from government or other organizations to enhance their socio – economic status.
Keywords: Barrage; Livelihood; Socio - economics; Thondaimanaru lagoon